Developing growth nutrient through rapid transformation of digital marketing: a comprehensive study on Nido FortiGrow - Rahi, Mahmuda Akter (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.